Answer:
A = 192
Step-by-step explanation:
r = 16/2 = 8
A = 3x(8)^2
8^2 = 64
A = 3 x 64 = 192
Answer:
Step-by-step explanation:
Multiply each term of the first polynomial with the second polynomial. Then combine the like terms.
(3a<em>² + 5a - 2)* (5a² -3a + 4)</em>
<em> = 3a² *(5a² -3a + 4) + 5a*(5a² -3a + 4) - 2*(5a² -3a + 4)</em>
<em>=3a²*5a² - 3a*3a² + 4*3a² + 5a*5a² - 3a*5a + 4*5a + 5a²*(-2) - 3a*(-2) + 4*(-2)</em>
<em>=15a⁴ - 9a³ + 12a² + 25a³ - 15a² + 20a - 10a² + 6a - 8</em>
<em>= 15a⁴ </em><u><em>- 9a³ + 25a³</em></u><em> +</em><u><em> 12a² - 15a² - 10a²</em></u><em> +</em><u><em> 20a +6a </em></u><em>- 8</em>
<em>= 15a⁴ + 16a³ - 13a² +26a - 8</em>
Answer:
1.861(10²)
Step-by-step explanation:
Proper scientific notation only has the ones place and decimals. To get the same value again, we would need the exponent to be 2 and not -2.
X= cost per cherry pie
y= cost per pumpkin pie
NICOLE
1x + 9y= $60
LISA
11x + 4y= $90
STEP 1
multiply Nicole's equation by -11
-11(1x + 9y)= -11($60)
multiply -11 by all terms
(-11 * x) + (-11 * 9y)= (-11 * 60)
-11x - 99y= -660
STEP 2
add Nicole's new equation from step 1 to Lisa's equation to solve for y (using the elimination method)
-11x - 99y= -660
11x + 4y= 90
the x terms "cancel out"
-95y= -570
divide both sides by -95
y= $6 per pumpkin pie
STEP 3
substitute y value into either original equation to solve for x
x + 9y= $60
x + 9(6)= 60
x + 54= 60
subtract 54 from both sides
x= $6 per cherry pie
CHECK
11x + 4y= $90
11(6) + 4(6)= 90
66 + 24= 90
90= 90
ANSWER: Each cherry pie costs $6 and each pumpkin pie costs $6.
Hope this helps! :)
Answer:
65.63 cm or 65 5/8 cm
Step-by-step explanation:
volume of a rectangular prism = whl
w= 7 1/2
h = 2 1/2
l = 3 1/2
w x h x l